2012
DOI: 10.4103/2156-7514.96546
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postnatal Schizencephaly Findings by 2D and 3D Ultrasound: Pictorial Essay

Abstract: Schizencephaly is a brain-destructive lesion relating to clefts in the fetal brain that usually communicate with the ventricular system, subarachnoid space, or both. It presents as two types: Type I (closed) and Type II (open). During pregnancy, it may be suspected in the course of ultrasonography, which highlights ventricular dilatation and brain abnormalities. Usually, the diagnosis is confirmed postnatally using trans-fontanel ultrasonography. The etiology of schizencephaly is still unknown, but it may be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…Fetal central nervous system (CNS) malformations is a common congenital anomaly, with an incidence of 0.14% − 0.16% among live births and 3% − 6% among stillbirths [1] . CNS malformations can lead to intellectual, motion and behavioral disorders and even death in children, causing distress and representing a heavy burden on children, families and society [2] . Thus, scholars in China and other countries have paid substantial attention to developing prenatal diagnostic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal central nervous system (CNS) malformations is a common congenital anomaly, with an incidence of 0.14% − 0.16% among live births and 3% − 6% among stillbirths [1] . CNS malformations can lead to intellectual, motion and behavioral disorders and even death in children, causing distress and representing a heavy burden on children, families and society [2] . Thus, scholars in China and other countries have paid substantial attention to developing prenatal diagnostic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, schizencephaly can be seen in association with Dandy-Walker malformation, cerebellar agenesis, gastroschisis, facial clefts, and absence of septum pellucidum. 4,5,17,18 Moreover, schizencephaly, as previously stated, is thought to be a part of global dysgenetic event in the fetal brain. 18,19 In our series, the most common cerebral malformation accompanying schizencephaly was polymicrogyria, cerebellar hypoplasia, and mega cisterna magna.…”
Section: Discussionmentioning
confidence: 85%
“…Very recently, Rios et al reported six cases of schizencephaly and stated that in all their cases, prenatal diagnosis is suspected or made by 2- and 3-dimensional ultrasonography. 5 In this series, all cases were diagnosed prenatally. Although definitive diagnoses were made in two cases with sonography, fetal MRI was the principal method for the diagnosis in the remaining three cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Agenesia nas (8) , y la revisión de la literatura inglesa hasta el año 2012 da un total de 52 casos diagnosticados prenatalmente en 24 publicaciones. La revisión de las bases de datos latinoamericanas (Scielo, Redalyc, Alicia, Latindex), hasta el año 2018, solo muestra 3 publicaciones de diagnóstico prenatal (10)(11)(12) , que añaden 8 casos a la literatura mundial. No hemos encontrado caso o serie de casos publicados en el Perú.…”
Section: Alteración Unilateral Bilateralunclassified